Acquiescent and defensive silence in an Indonesian context - Riantoputra, Corina D.; Maharisa, Widya; Faridhal, Tytania (Makara Human Behavior Studies in Asia, 2016)
Although employee silence is already well-known to cause harms to both employees and organizations, less is known about the individual and situational factors that can influence it. This study reveals the relationships among acquiescent silence, defensive silence, psychological contract breaches, job-based psychological ownership, voice efficacy, psychological safety and task cohesion. Employing scales with good reliability scores (α between 0.8 to 0.95), we conducted a survey on a sample of of 260 public employees of an Indonesia’s government institution. Analysis indicates that (1) individual factors (voice efficacy and psychological contract breach) and situational factors (task cohesion and psychological safety) work hand in hand to affect silence behavior; and (2) job-based psychological ownership has no relationship with acquiescent and defensive silence. This paper discusses (1) the importance incorporating individual and situational factors in understanding silence behavior; and (2) the collectivistic nature of Indonesian people that may contribute to the importance of situational factor (i.e., task cohesion) on silence behavior well and beyond psychological ownership.